Peningkatan Hasil Belajar Etika Profesi Keguruan melalui PjBL di PGSD Universitas Cenderawasih - Rusli, Tiffany Shahnaz; Yuliana, Chelsi; Ali, Aisyah; Sumawan, Sumawan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
Currently, educators or lecturers are required to convey differentiated learning methods and use the Project Based Learning (PjBL) learning model. Knowing each students strengths and weaknesses helps lecturers create learning designs that can improve learning outcomes that have been determined, especially in course on ethics and the teaching profession. In the PjBL model there are stages or steps to solve current problems from the material that has been prepared. By solving problems in groups and creating a work in the form of a product, students will work together and be actibe to complete their assignments. This research activity aims to determine the improvement in learning outcomes using the PjBL learning model in the ethics and teaching profession course. The research method that will be used is the qualitative method, which is a research method that emphasizes analysis or description. The research results clearly show a positive impact on improving student learning outcomes.